2019
DOI: 10.1038/s41598-019-45728-5
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Flavones from Primula macrocalyx as Inhibitors of OAT1 and OAT3 and as Antifungal Agents against Candida rugosa

Abstract: A bioactivity guided program exploring the interaction of phytochemicals in the entire plant Primula macrocalyx with the organic anion transporters (OAT1 and OAT3) and microorganisms led to the elucidation of ten known flavones ( 1 – 4 , 6 – 10 , 12 ) and two previously undescribed flavones ( 5 , 11 ). The structures of the compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…We established the homology models of OAT1 and OAT3 using PiPT (PDB ID 4J05) and MdfA (PDB ID 4ZP2) as templates, respectively, and identified various OAT inhibitors from a library of 270 natural products 38 . The inhibitory mechanisms for the identified OAT inhibitors were also investigated 35 , 39 , 40 . Additionally, we showed that inhibition of OATs could be a potential strategy to protect against kidney injuries induced by xenobiotics.…”
Section: Transporter-mediated Ndismentioning
confidence: 99%
“…We established the homology models of OAT1 and OAT3 using PiPT (PDB ID 4J05) and MdfA (PDB ID 4ZP2) as templates, respectively, and identified various OAT inhibitors from a library of 270 natural products 38 . The inhibitory mechanisms for the identified OAT inhibitors were also investigated 35 , 39 , 40 . Additionally, we showed that inhibition of OATs could be a potential strategy to protect against kidney injuries induced by xenobiotics.…”
Section: Transporter-mediated Ndismentioning
confidence: 99%
“…As such, flavones are often classified as phytoestrogen [27]. In addition, flavones exhibit antifungal and antidiabetic properties [24,28]. Flavones are also known to be used as antioxidants because they can inhibit the action of the xanthine oxidase enzyme from producing Reactive Oxygen Species (ROS).…”
Section: Flavonesmentioning
confidence: 99%
“…Phytochemical studies on Primula species have mainly revealed saponins and phenolic compounds including phenolic acids, phenolic glycosides, and especially flavonoids, along with glucosinolates, carotenoids, and essential oils [20–26] . Triterpenoid saponins; pridentigenins A–E, denticulatin, primulanin, saxifragifolia B, macrophyllicin, primacrosaponin, priverosaponin B, priverosaponin B‐22 acetate, primulasaponin I and primulasaponin II were detected from several Primula species such as P. denticulate , P. macrophyllata , P. elatior , and P. veris [25,27–30] .…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] Phytochemical studies on Primula species have mainly revealed saponins and phenolic compounds including phenolic acids, phenolic glycosides, and especially flavonoids, along with glucosinolates, carotenoids, and essential oils. [20][21][22][23][24][25][26] Triterpenoid saponins; pridentigenins A -E, denticulatin, primulanin, saxifragifolia B, macrophyllicin, primacrosaponin, priverosaponin B, priverosaponin B-22 acetate, primulasaponin I and primulasaponin II were detected from several Primula species such as P. denticulate, P. macrophyllata, P. elatior, and P. veris. [25,[27][28][29][30] While primulasaponin I was previously identified from P. vulgaris, [31] primulasaponin I methyl ester was synthetically prepared from primulasaponin I by Çalış et al [30] However, in this current research, primulasaponin I methyl ester was first reported naturally from P. vulgaris.…”
Section: Introductionmentioning
confidence: 99%